The Adverse Effects of Underwater Sound upon Fishes and Invertebrates - D Hawkins Anthony (International Marine Science Journal, 2023)
Underwater sound is very important to most fishes and invertebrates. Underwater sounds from both natural and human sources can have adverse effects upon aquatic animals, and especially fishes, and invertebrates. It is important to examine the effects of sound upon them, and especially the effects of sounds derived from human sources (anthropogenic sounds). It may be possible to introduce protective regulations to reduce their effects. Fishes and invertebrates can detect underwater sounds, and they use sound to obtain key information about the environment around them. They can also make sounds themselves, especially during their spawning. Sounds travel rapidly over great distances in water and can provide detailed information to these animals on the presence of prey, predators, and related species, while the overall acoustic scene provides them with key information about their environment. Anthropogenic sounds can be very harmful, and it is therefore important to deal with them. A succession of reports and scientific papers have emphasised the risks to these animals from exposure to man-made sounds or noise and will be mentioned in this paper, which also deals with the Criteria and Metrics for assessing the effects of underwater sound on fishes and invertebrates.
Keywords: Fishes